DEVELOPMENT OF INTEGRATED NATURAL SCIENCE ELECTRONIC CHAPTER BOOK WITH CONTEXTUAL APPROACH ON THE MATERIAL GLOBAL WARMING FOR CLASS VII SMP - Septi Namori J.J; Relsas Yogica (Universe, 2022)
The study was back-to-back by an impractical and united material teach the high school for middle school science. That effort to do is to develop the integrated science teaching material. One is the material to be developed is the chapter of the electronic book. As for the purpose of this research to develop a textbook integrated science electronic with approaches contextual on global warming materials for class VII junior participants. The kind of research used was to design research with using plomp model development. The data is qualitative and quantitative. Phase chapter electronic book phase chapter was validated by two people the validator who specialized in his field covered six aspects of worthiness, that is aspects of eligibility, compliance, worthiness of presentation, worthiness cropability, alignment, and contextual worthiness. At the stsge assessment electronic chapter book is evaluated witth an instrument evaluation one to one individual. This study result from nilai`s validity of 78,43% in valid categories. This is can be concluded that electronic chapter book integrated science with contextual approach to heating matter a global developed meets valid criteria.